It’s In Our Hands: facilitating agency, personal connections and collective cohesion in climate education through board game play - Annie Padwick; Emma P. Hocking; Joe Shimwell; Carol Davenport; Julia Bourne; Kayleigh Ransome; Chelsea Baxter; Alan Ramsay; Edward Blazey (Journal of Environmental Studies and Sciences, 2026)
The complexity of climate change can make it difficult for younger children to engage with it. We present the co-design and piloting of a serious game about climate change, designed for civic as well as educational purposes. An existing game developed by the authors was revised through co-design with children, teachers and outreach practitioners, facilitated by a participatory design agency. Co-design identified nine key areas of improvement of the game: title; geographic location; language; teacher resources; classroom pedagogy; scoring; board; accompanying cards; and scalability. The language and design of the final version was revised to ensure it was accessible to children and could be facilitated by teachers in a classroom setting. Piloting was undertaken with a further 73 primary school children in two schools in Northeast England to assess whether gameplay in classrooms could generate the desired intrapersonal and learning outcomes. Ethnographic analysis of data indicates the game can help children to develop their agency in climate-decision making, foster real-world connections with climate change, and realise the collective cohesion and urgency needed to tackle climate change, as well as develop understanding of the climate change system. Other more emergent themes included the parallels between game discussions and real-world decision making on climate change, including the important role of strong leaders and advocates, and the level of responsibility and ownership children took in the game.

Age, pair tenure and parenting, but not face identity, predict looking behaviour in a pair-bonded South American primate - Allison R. Lau; Alexander Baxter; Shuyu He; Louise Loyant; Chelsea A. Ortiz-Jimenez; Melissa D. Bauman; Karen L. Bales; Sara M. Freeman (Animal Behaviour, 2024)